THE EFFORTS TO TERMINATE THE SITUATION WITH NO-CITIZENSHIP AND HUMAN RIGHTS VIOLATION OF ROHINGYA ETHNIC - Sefriani Sefriani (Jurnal Dinamika Hukum, 2015)
The refusal to recognize citizenship of Rohingnya ethnic by Myanmar government caused this ethnic without national and international protection. Statelessness situation is also became the entry point of other violation of human right such as ethnic cleansing and genocide which caused this ethnic became refugee. Some solutions offered to end this situation are: cooperate with UNHCR provide temporary shelter for those people; urge UNHCR granted refugee status for Rohingya; urge ASEAN conducted humanitarian diplomacy pursued Myanmar recognized citizenship of Rohingnya ; applied R to P to end the gross violation on human right toward Rohingnya if the threshold were fulfilled.Keywords: Rohingnya, citizenship; human right